Tungsten disulfide (WS2) is a highly active co-catalyst in Fe(III)/H2O2 Fenton-like reactions for efficient acetaminophen degradation - He, Dongqin; Wang, Dongli; Luo, Hongwei; Zeng, Yifeng; Zeng, Ganning; Li, Jun; Pan, Xiangliang (The Science of the total environment, 2023)
The most important factor that restricts the decomposition of H2O2 in the Fe3+/H2O2 reaction is the slow cycling efficiency of reducing Fe3+ to Fe2+. In this study, the addition of tungsten disulfide (WS2) as a co-catalyst achieved a rapid cycling of the reaction rate-limiting step and a significant enhancement of H2O2 decomposition, which resulted in the effective degradation of acetaminophen (APAP). Results show that 99.6% of APAP (5 mg L−1) could be degraded by H2O2/Fe3+/WS2 system within 2.5 min. The conversion of Fe3+ to Fe2+ occurred mainly on the surface of WS2 due to the redox reaction of the exposed W4+ active sites with Fe3+ after the unsaturated S atoms were bound to protons. Electron paramagnetic resonance (EPR) and radical quenching experiments evaluated the contribution of hydroxyl radical (•OH) and superoxide radical (O2•−) in the degradation of pollutants. WS2 showed good recoverability after four cycles of the reaction. This study provides a new perspective to improve the efficiency of Fe3+/H2O2 and provides a reference for the involvement of transition metal sulfides in advanced oxidation processes (AOPs). [Display omitted] •Addition of tungsten disulfide as a co-catalyst achieved a rapid Fe3+/Fe2+ cycling.•99.6 % of acetaminophen (5 mg L−1) could be degraded within 2.5 min by the system.•Fe3+/Fe2+ cycling was due to the redox reaction of exposed W4+ active site with Fe3+.•The contribution of hydroxyl radical (OH) and superoxide radical (O2−) was identified.